INISIATIF-INISIATIF LOKAL DALAM PENYELESAIAN KONFLIK DAERAH PENANGKAPAN IKAN DI PESISIR SAMBOJA, KUTAI KARTANEGARA (Local Initiatives Inconflict Resolution of Fishing Ground in The Coastal of Samboja, Kutai Kartanegara) - ETIK SULISTIOWATI NINGSIH; NURUL OVIA OKTAWATI; OON DARMASYAH; DONI DARMASETIADI (Universitas Mulawarman (University of Mulawarman), 2022)
With a qualitative research approach, this study aims to obtain information from key informants regarding how to solve maritime spatial conflicts in Samboja District. In-depth interviews were conducted with the Head of Tanjung Harapan Village, the Head of UPT Air Brackish and the head of the fishing group. Recorded data were transcribed and analyzed deductively based on the themes and categories found. This study found that that the resolution of fishing zone conflicts in Samboja District is carried out horizontally and vertically. Horizontally, conflict resolution is carried out by dividing the fishing ground based on the type of fishing gear and fishing capacity. Active fishing gear is not placed near to passive fishing gear. On the other hand, the greater the fishing capacity, the farther the area of operation is from the coast. Vertically, the same type of fishing gear is arranged according to its depth so that several gears overlap but do not interfere with each other. Those local and participatory conflict resolution initiatives are important to achieve sustainable and equitable use of coastal and marine areas.